IMPLEMENTASI NILAI SILA KELIMA PANCASILA DALAM PENDIDIKAN PPKN SEKOLAH DASAR UNTUK MENGURANGI KESENJANGAN SOSIAL - Juan Vito Simanjuntak; Muhammad Iqbal; Maharani Br Purba; Nurdilla Ramadhani; Risky C Pratama Manullang; Tiara Niammusyfah Pasaribu (Jurnal Merah Putih Sekolah Dasar, 2025)
This study aims to analyze the implementation of the Fifth Principle of Pancasila values in Civic Education (PPKn) learning in elementary schools as an effort to reduce social inequality from an early age. Social inequality remains a significant issue in Indonesian society and may lead to injustice in various aspects of life. Elementary education plays a strategic role in instilling social justice values as a foundation for students’ character development. This research employs a qualitative descriptive method through a literature review by examining scientific journals, books, and policy documents related to Pancasila, character education, and Civic Education learning in elementary schools. The findings indicate that the implementation of social justice values can be carried out through the integration of PPKn learning materials, contextual learning approaches, teacher role modeling, and the habituation of fair attitudes, tolerance, and social empathy in school life. Civic Education learning based on Pancasila values is expected to foster students’ awareness of social justice and contribute to reducing social inequality in the future.